Effect of Physical Parameters and Training Load on Patellar Tendon Stiffness in Professional Athletes - Claudia Römer; Enrico Zessin; Julia Czupajllo; Thomas Fischer; Bernd Wolfarth; Markus Herbert Lerchbaumer (Diagnostics, 2023)
Background: Injuries of the patellar tendon commonly occur as a result of mechanical loading of the tendon during physical activity. Shear wave elastography (SWE) is an established technique for assessing tendon stiffness, and has good interindividual reliability. The aim of this study was to investigate the impacts of physical parameters and different sports on patellar tendon stiffness in professional athletes using SWE. Methods: Standardized patellar tendon SWE was performed in a relaxed supine position with a small roll under the knee (20° flexion) in 60 healthy professional athletes (30 female, 30 male). Multiple linear regression was performed for patellar tendon stiffness including gender, age, body mass index (BMI), and type of sport. Results: Patellar tendon stiffness showed no significant difference between female (3.320 m/s) and male (3.416 m/s) professional athletes. Mean age (female: 20.53 years; male: 19.80 years) and BMI (female: 23.24 kg/m2; male: 23.52 kg/m2) were comparable. Female professional athletes with oral contraceptive (OC) intake showed higher patellar tendon stiffness than athletes without OC intake (3.723 versus 3.017; p = 0.053), but not significantly. Conclusion: In professional athletes, there are no significant differences in patellar tendon stiffness according to gender, age, BMI and type of sport (handball, volleyball, soccer, sprint, hammer throw). Oral contraceptives may not have an impact on patellar tendon stiffness in female athletes. Further studies are necessary.